2007
DOI: 10.1111/j.0021-9029.2007.00143.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Disability as Related to Medical and Social Factors

Abstract: This study addressed self-perception of disability and the belief that others perceive one to have a disability. Factors from the medical and social models of disability were tested to determine if social factors still play a role in such perceptions when controlling for medical factors. Cross-sectional data from the 1994-1995 National Health Interview Study on Disability (NHIS-D) provided a stratified random sample of 25,805 noninstitutionalized adults. Logistic regression models were used to demonstrate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 17 publications
1
22
0
1
Order By: Relevance
“…In our initial hypothesis, it had been labeled self-protection from negative judgments from others , which consisted in evaluating the ability of the individual to accept themselves without the worry of being negatively evaluated by others. However, after an analysis of the discussions from the two focus groups and in accordance with studies of Brittain [45] , Hughes [46] , Lobianco and Sheppard-Jones [47] , Sahin and Akyol [48] , Tripp [49] , and Watson [50] , we found that for individuals with disabilities, an important source of negative judgment comes from social stigmas. Stigma is an attribute that others perceive to be deeply discrediting [51] - [52] .…”
Section: Study 1: Item Generationsupporting
confidence: 75%
“…In our initial hypothesis, it had been labeled self-protection from negative judgments from others , which consisted in evaluating the ability of the individual to accept themselves without the worry of being negatively evaluated by others. However, after an analysis of the discussions from the two focus groups and in accordance with studies of Brittain [45] , Hughes [46] , Lobianco and Sheppard-Jones [47] , Sahin and Akyol [48] , Tripp [49] , and Watson [50] , we found that for individuals with disabilities, an important source of negative judgment comes from social stigmas. Stigma is an attribute that others perceive to be deeply discrediting [51] - [52] .…”
Section: Study 1: Item Generationsupporting
confidence: 75%
“…The social model, on the other hand, calls attention to policies, institutional practices and physical environments that restrict access and systematically discriminate against those who fail to conform to normal standards of form and function (Scotch & Schriner, 1997;Shakespeare, 2006). Such disparate conceptions of disability affect perceptions of self and others and can have a pervasive influence in the shaping of identity (LoBianco & Sheppard-Jones, 2007;Smart, 2009).…”
Section: Coping With Disability Stigma: Individualistic and Collectivmentioning
confidence: 99%
“…The social model holds that disability is a product of the ongoing interaction between individuals and their environments (DePoy & Gilson, 2004;Gill et al, 2003;Hahn, 1999;LoBianco & Sheppard-Jones, 2007;Longmore, 1995; National Institute on Disability and Rehabilitation Research [NIDRR], 1999;Smart, 2001;Smart & Smart, 2007). This model focuses on the dynamic interactions of their individual characteristics (e.g., conditions, functional status, personal and social qualities) with the natural, built, cultural, and social environments (NIDRR, 1999).…”
Section: Guideline 1 Psychologists Strive To Learn About Various Aismentioning
confidence: 99%